2017
DOI: 10.1016/j.envpol.2016.10.099
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical reactions between mercury (Hg) and dissolved organic matter decrease Hg bioavailability and methylation

Abstract: Atmospheric deposition of mercury (Hg) to surface water is one of the dominant sources of Hg in aquatic environments and ultimately drives methylmercury (MeHg) toxin accumulation in fish. It is known that freshly deposited Hg is more readily methylated by microorganisms than aged or preexisting Hg; however the underlying mechanism of this process is unclear. We report that Hg bioavailability is decreased by photochemical reactions between Hg and dissolved organic matter (DOM) in water. Photo-irradiation of Hg-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 49 publications
1
32
0
Order By: Relevance
“…The effects of cultivation ages on soil properties and HM concentration may suggest potential association between them. Previous work revealed that HM concentrations and bioavailability are closely related to soil physicochemical properties, e.g., OM contents (Luo et al, 2017), pH (Jackson et al, 1993;Liu et al, 2013) and nutrient concentrations. The effect of soil properties on HM concentrations in soil could result from the biogeochemical processess in soil including adsorption, precipitation and complexation reaction with soil components (Wang et al, 2015a;2015b;.…”
Section: Correlation Between Soil Properties and Hmsmentioning
confidence: 99%
“…The effects of cultivation ages on soil properties and HM concentration may suggest potential association between them. Previous work revealed that HM concentrations and bioavailability are closely related to soil physicochemical properties, e.g., OM contents (Luo et al, 2017), pH (Jackson et al, 1993;Liu et al, 2013) and nutrient concentrations. The effect of soil properties on HM concentrations in soil could result from the biogeochemical processess in soil including adsorption, precipitation and complexation reaction with soil components (Wang et al, 2015a;2015b;.…”
Section: Correlation Between Soil Properties and Hmsmentioning
confidence: 99%
“…Therefore, the DOM increased concentration may inhibit Hg adsorption dramatically. In addition to DOM stabilizing Hg in dissolved phase, the formation of β-HgS particles from Hg 2 + interacting with DOM was found in others [49,50]. The particle size of β-HgS nanoparticles was around 3-5 nm reported by Manceau et al [50].…”
Section: "Hg + Dom" Conditionmentioning
confidence: 81%
“…11,17,19,46 Photochemical processes may produce inert Hg products (nonreducing or slower reducing components), resulting in differences between biological and photochemical reduction. 47,48 The fundamental mechanisms involved in the biological reduction process remain poorly understood. We estimated the contributions of microalgae, bacteria, SPM, and DOM/extracellular substances to dark Hg 2+ reduction in natural seawater.…”
Section: ■ Discussionmentioning
confidence: 99%